HPB P26 C-reactive protein/albumin ratio may be helpful for assessing suitability for resection in patients with pancreatic head malignancy. (7th December 2022) - Russell, Thomas; Labib, Peter; Aroori, Somaiah
Abstract: Background: Prior studies have suggested that high preoperative C-reactive protein/albumin ratio (CAR) correlates with reduced survival following pancreatoduodenectomy (PD) performed for malignancy affecting the pancreatic head, since this feature is characteristic of a more aggressive tumour. Various cut-off thresholds have been suggested, with a threshold of 0.2 (x10–3) considered in several publications. This study aimed to compare the five-year survival of PD patients with high preoperative CAR (≥0.2) to those with low preoperative CAR (<0.2). Methods: Data was extracted from the Recurrence After Whipple's (RAW) study, a multicentre retrospective cohort study of outcomes following pancreatoduodenectomy performed for pancreatic head malignancy (29 centres in 8 countries, n=1, 484). Patients were grouped by their underlying cancer type and divided into "high" and "low" CAR groups. Five-year survival rates were compared using Fisher's exact test. Results: Out of 1484 patients, 885 (59.6%) had pancreatic ductal adenocarcinoma (PDAC), 394 (26.5%) had ampullary carcinoma (AA) and 205 (13.8%) had cholangiocarcinoma, and CAR data was available for 48.8%, 42.6% and 44.4% of patients, respectively. In patients with PDAC, the median CAR was 0.2 (range: 0.0–23.8) and low CAR was associated with significantly improved five-year survival (32.6% vs 18.0%, p=0.0006). In those with AA, median CAR was 0.2 (range 0.0–19.5), those with low CAR had improved five-year survival but this was not quite significant (60.3% vs 46.7%, p=0.09). Median CAR was 0.3 in those with CC (range: 0.0–14.3) but this did not appear to affect survival (33.9% vs 30.8%, p=0.7). Conclusions: In our multicentre study, PD patients with a histological diagnosis of PDAC had significantly improved five-year survival rates if they had a low CAR. CAR is a useful prognostic indicator in these patients and may be helpful for assessing patient's suitability for resection.